What is a Preschool Teacher’s "Ideal Role"? Case Study based on Kindergarten Regulation System - He, Jing; Wang, Ping (International Journal of Social Sciences and Public Administration, 2024)
Under the background of high-quality development of preschool education, the construction of a preschool teacher team is the critical support, and the construction of the ideal role of preschool teachers is an essential means of a high-quality teacher team. Based on the perspective of kindergarten norms and system cases, this paper takes the case norms of six kindergartens in Shandong and Tianjin as the research object and uses the case study method to show the reality of the ideal role of kindergarten teachers from the perspective of kindergartens. The results show that from the perspective of kindergarten practice, the ideal role of preschool teachers is described through strict role norms, kindergarten rules, class rules, new teachers’ induction education and training, rewards, and punishments. Based on the expectation, relationship, status, and behavior of the social role theory, this paper disassembles and analyzes the ideal role of preschool teachers in detail and finds that the ideal role of preschool teachers in the concrete work practice of kindergartens is bound to be restricted by various systems and norms in kindergartens, and presents a variety of ideal roles.